2007
DOI: 10.1258/000456307780480918
|View full text |Cite
|
Sign up to set email alerts
|

Osteopontin and C-reactive protein in Egyptian patients affected with tuberculous and malignant pleural effusion

Abstract: AddressesBackground The first step in the evaluation of patients with pleural effusion is to determine whether the effusion is a transudate or an exudate. Osteopontin (OPN) is a pleiotropic integrin-binding protein with many functions. We assessed pleural effusion and serum concentrations of OPN and C-reactive protein (CRP) in patients with different types of pleural effusions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
9
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 27 publications
1
9
0
Order By: Relevance
“…As far as the mechanisms underlying the formation of pleural effusions, it was interesting that in patients with exudative pleural effusions, median PF OPN was more than 110 times higher than the serum OPN concentration. In addition, PF OPN levels were 10‐fold higher in pleural exudates than in transudates, an observation that is in agreement with a previous study 18 . PF OPN levels were also significantly correlated with markers of pleural space inflammation and enhanced vascular permeability, the pathogenetic hallmarks of exudative pleural effusions 16 .…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…As far as the mechanisms underlying the formation of pleural effusions, it was interesting that in patients with exudative pleural effusions, median PF OPN was more than 110 times higher than the serum OPN concentration. In addition, PF OPN levels were 10‐fold higher in pleural exudates than in transudates, an observation that is in agreement with a previous study 18 . PF OPN levels were also significantly correlated with markers of pleural space inflammation and enhanced vascular permeability, the pathogenetic hallmarks of exudative pleural effusions 16 .…”
Section: Discussionsupporting
confidence: 91%
“…Unexpectedly, patients with benign disease had higher serum OPN levels than those with malignant pleural effusions, a finding that contrasts with previous reports 3,4,18 . This discrepancy may be related to the fact that in previous studies the benign group consisted of normal subjects and patients with asbestos‐related benign pleural disorders.…”
Section: Discussionmentioning
confidence: 56%
“…Recently, Elsammak et al have reported that OPN concentration was significantly elevated in MPEs compared with transudative effusion for Egyptian patients [22]. However, there have been no studies revealing the role of OPN in the formation of MPE associated with lung cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Morsi et al determined the SPP1 concentrations of serum and pleural effusion from 80 patients (20 with transudative effusion; 30 with MPE, including 14 patients with NSCLC; 30 with tuberculous effusion) using ELISA. Their findings suggested that there was minimal difference between the serum SPP1 levels and effusion/serum SPP1 ratios of the patients with MPE and those with tuberculous effusion [24]. However, Moschos et al measured serum and pleural effusion levels of SPP1 from 109 patients (42 with MPE, including 19 patients with NSCLC; and 67 with benign diseases) using ELISA, and found that patients with MPE had higher pleural effusion levels and lower serum levels of SPP1 than those with benign disease [25].…”
Section: Discussionmentioning
confidence: 99%
“…The cutoff value determined in this study is specific but not sensitive enough, which might have resulted in false-negative results in patients with low SPP1 levels. The reasons for low sensitivity may be the following: a) Interindividual differences may be enhanced when the sample amount is small; b) SPP1 is also related to the formation of lung granulomas because of its role in cellular immunity [26], as research has shown that circulating SPP1 levels in patients with pulmonary tuberculosis were significantly higher than in healthy controls, while the levels might reflect the activity of tuberculosis [27]; and c) SPP1 levels in exudative pleural effusion (e.g., tuberculous pleural effusion) were significantly higher than those in transudative hydrothorax [24,25]. There is a high prevalence of tuberculous pleurisy in China, and patients with tuberculous pleurisy in our study accounted for as many as 75% of together with the control patients, while patients with transudative hydrothorax only accounted for 8.3%.…”
Section: Discussionmentioning
confidence: 99%